Advance planning decisions at Cordoba and Gualdaquivir Health District, Spain - Jiménez Rodríguez, José Manuel (Acta Bioethica, 2017)
Objectives: Determine the knowledge, attitude and advance care planning in primary care and to identify associated factors. Material /Methods: Type of study: Cross-sectional multicentric study. Study population: Physicians and nurses of 15 Clinical Management Units at Cordoba-Guadalquivir Health District (Spain). Sampling: Multistage with N=269. Tools: Validated questionnaire. Analysis: Descriptive and bivariate statistical analyses were done. Results: Mean age of 51 years professional (SD 8.2) and 60.9% of them were women. About 55.8% of participants were physicians and 79.3% had permanent posts. Mean working years was 23.5 (SD 9.4) and about 50.9% of participants worked at rural areas. Mean knowledge score was 5.1 (SD 2.09). 98.4% believe early vital will is regulated in Andalusia. About 56.9% have not read the regulatory document and 78.1% have not read the planning guidebook. More than 65% don’t know the corresponding registry office. 89.3% do not plan in the last year; who planned did that <3 times. The p value of planning is: (p = 0.838) about sex; (p = 0.521) age; (p = 0.841) scope of work, (p = 0.543) professional category; (p = 0.934) years of service; (p = 0.210) type of contract. Conclusions: Few medical practitioners plan with the patient. No independent study identifies factors.